Determining Honey Adulteration by Seeding Method: an Initial Study with Sunflower Honey - Kurt, Abdullah; Palabiyik, Ibrahim; Gunes, Recep; Konar, Nevzat; Toker, Omer Said (SPRINGER, 2020)
In the present study, a novel method was developed to determine honey adulteration. Natural sunflower honey (A), adulterated honey (B), indirectly adulterated honey obtained by feeding of bee colonies using sugar syrup (C), mixtures of them (AB and AC), and two additional natural sunflower honey samples coming from different geographical regions (D and E) were examined after seeding at different levels (1, 5, 10%, w/w) of crystallized honey. The physico-chemical property, FT-IR spectra, thermodynamic property (T-p and Delta H), flow behavior [storage (G ') and loss (G '') modulus], and microstructural changes of the samples were investigated. According to the obtained results, natural sunflower honeys showed different visco-elastic and flow behaviors from adulterated honeys. The microstructure properties were also different and more homogeneous, and faster crystallization was detected in natural honey (A). The results of this study notably show that honey adulteration can be determined by examining honey crystallization behaviors. Therefore, it is thought that the industry will benefit from this easy and simple method instead of time-consuming, expensive, and complex methods used for determining honey adulteration.
Keywords: Honey; Adulteration; Crystallization; Rheology; DIFFERENTIAL SCANNING CALORIMETRY; CANE SUGAR ADULTERATION; FRUCTOSE CORN SYRUP; THERMAL-PROPERTIES; ULTRASOUND; STARCH; Food Science & Technology